PENGARUH HARGA, LOKASI, BANGUNAN DAN LINGKUNGAN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN RUMAH TIPE 70 DI KOTA PONTIANAK - DEWI B11110054, IRA CITRA (Jurnal Manajemen Update, 2014)
The purpose of this study is to determine the impact of variable price, location, building, and the environment of the home purchase decision type 70 in the city of Pontianak. Respondents were taken from three different locations, namely at the downtown location, the city center and suburbs. Methods used in this research is quantitative research and sampling techniques using purposive sampling method, by taking 30 samples at each study site, so that the sample was obtained by 90 people. This watchfulness uses doubled linear regression analysis with program SPSS for Mac version 20. The results from this research that there are three variables that impact purchasing decision. The variables are the price with the coefficient of 0,828 and significance of 0,001, the location variable with coefficient 0,190 with a significance of 0,001, the building variable with coefficient 0,198 with significance of 0,007 and variables that do not have positive impact is the environment variable with coefficient 0,089 with aÂ  significance of 0,112 > 0,05. Using a significance test, results are declared significant if the significance value < 0,005. The test results stated that the price, the location, the building was significant and positive impact on purchasing decisions and stated that the environment variable is not significant so it doesnâ€™t have positive impact on home purchase decisions type 70 in the city of Pontianak. Key Word :Price, Location, Building, Environment